EFFECT OF RELATIVE HUMIDITY ON CREEP-SHRINKAGE BEHAVIOUR OF COMPOSITE TALL BUILDINGS - SHARMA, RAVI KUMAR (2013)
RELATIVE HUMIDITY OF ENVIRONMENT AFFECTS CREEP AND SHRINKAGE BEHAVIOUR OF A CONCRETE MEMBER OF COMPOSITE TALL BUILDINGS. THESE BUILDINGS ARE MORE PRONE TO REDISTRIBUTION OF FORCES AS ADJACENT STEEL COLUMNS AND RCC SHEAR WALLS HAVE QUITE DIFFERENT CHARACTERISTICS.&NBSP;IN THIS PAPER, STUDY IS CARRIED OUT TO EVALUATE THE EFFECT OF RELATIVE HUMIDITY OF ENVIRONMENT FOR A COMPOSITE BUILDING USING ANALYTICAL PREDICTION MODEL, CEB-FIP UPDATED 1999 AS THE FACILITY OF SHORT TERM TESTING MAY NOT BE ALWAYS AVAILABLE AND THUS, PREDICTION OF CREEP AND SHRINKAGE OF CONCRETE AT ANY TIME BY EXTRAPOLATION IS NOT POSSIBLE. AN ACCURATE PROCEDURE, CONSISTENT PROCEDURE, CP AVAILABLE IN LITERATURE IS MODIFIED BY INCORPORATING ANALYTICAL PREDICTION MODEL CEB-FIP UPDATED 1999.&NBSP; IT HAS BEEN SHOWN THAT DIFFERENTIAL DEFLECTIONS IN A COMPOSITE FRAME SHEAR WALL SYSTEM ARE SIGNIFICANTLY AFFECTED BY RELATIVE HUMIDITY. IT HAS BEEN FURTHER REPORTED THAT ALTHOUGH, THE STEEL COLUMNS HAVE ONLY ELASTIC DEFORMATION FOR THE CHOSEN COMPOSITE FRAME SYSTEMS, THERE IS SIGNIFICANT INCREASE IN DESIGN FORCES WHEN RELATIVE HUMIDITY DECREASES.&NBSP;